Instructional Explanations in the Disciplines - Stein, Mary Kay.; Kucan, Linda; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
In today$1 (Bs climate of accountability and standards, increasing attention is focused on teacher "quality," with less emphasis on what teachers actually do to interest and engage students in learning. This path-breaking volume addresses this research problem with a clear definition and a content-specific analysis of the most essential teaching moment$1 (Bthe instructional explanation$1 (Bfor vital new perspectives on educational method and process. Rich in examples from science, mathematics, and the humanities (and touching on areas of course development and pre-service training), Instructional Explanations in the Disciplines explores a variety of interactive contexts for teaching and learning, which may be collaborative between teachers, students, and others, performed in non-classroom settings, or assisted by technology. The book$1 (Bs subject-matter-specific framework reveals key elements in the process, such as carefully examining the question to be answered, making connections with what is already known, and developing examples conducive to further understanding. Among the topics covered: The model as a method of explanation in science How$1 (Band why$1 (Bteachers explain things as they do "Let us explain with you": introducing instructional explanations How families talk about art in museum settings, and what we can learn from it Developing writing skills through students$1 (Bgiving instructional explanations Instructional explanation in the context of learning and identity Instructional Explanations in the Disciplines is a valuable addition to the education library, giving researchers new methods of unpacking educational process as few books before it.s
Instructional Explanations in the Teaching and Learning of Science -- Introduction: Explaining Instructional Explanations -- What Kind of Explanation is a Model? -- Learning, Identity, and Instructional Explanations -- Learning Chemistry: What, When, and How? -- Negotiating the Goal of Museum Inquiry: How Families Engineer and Experiment -- Instructional Explanations in the Teaching and Learning of Mathematics -- A Framing of Instructional Explanations: Let Us Explain With You -- How and Why Do Teachers Explain Things the Way They Do? -- The Explanatory Power of Examples in Mathematics: Challenges for Teaching -- Using Designed Instructional Activities to Enable Novices to Manage Ambitious Mathematics Teaching -- Instructional Explanations in the Teaching and Learning of the Humanities -- Learning History and Learning Language: Focusing on Language in Historical Explanations to Support English Language Learners -- Instructional Explanations in a Legal Classroom: Are Students$1 (BArgument Diagrams of Hypothetical Reasoning Diagnostic? -- Connecting with Art: How Families Talk About Art in a Museum Setting -- Developing Writing Skills Through Students Giving Instructional Explanations.s
Keywords: Education; Educational psychology; Education; Teaching and Teacher Education; Educational Psychology; Learning & Instruction